Ag(I)-catalyzed heterocyclization/[3+2] cycloaddition of α-alkynylenones with β-enaminones: tandem access to highly substituted cyclopenta[c]furans - Vara, Vijay; Thete, Kishor R.; Panikar, Sera Deepu; Khan, Akram A.; Muthukrishnan, M. (Journal of Organic Chemistry, 2025)
A robust Ag(I)-catalyzed tandem heterocyclization/[3 + 2] cycloaddition of alpha-alkynylenones with beta-enaminones was developed, enabling efficient synthesis of cyclopenta[c]furans with good yields, operational simplicity, and broad substrate scope. In addition, it also presents an extended methodology to synthesize unsymmetrical tri(hetero)aryl methane having chromone and furan/pyrrole scaffolds by a slight modification of starting materials. Moreover, the synthesized cyclopenta[c]furans exhibit good fluorescence properties with quantum yields ranging from 0.33 to 0.53, as suggested by the photophysical studies.